Consensus-Based Guidelines for Best Practices in the Selection and Use of Examination Gloves in Healthcare Settings - Jorge Freitas; Alexandre Lomba; Samuel Sousa; Viviana Gonçalves; Paulo Brois; Esmeralda Nunes; Isabel Veloso; David Peres; Paulo Alves (Nursing Reports)
Background/Objectives: Healthcare-associated infections (HAIs) and antimicrobial resistance (AMR) present significant challenges in modern healthcare, leading to increased morbidity, mortality, and healthcare costs. Examination gloves play a critical role in infection prevention by serving as a barrier to reduce the risk of cross-contamination between healthcare workers and patients. This manuscript aims to provide consensus-based guidelines for the optimal selection, use, and disposal of examination gloves in healthcare settings, addressing both infection prevention and environmental sustainability. Methods: The guidelines were developed using a multi-stage Delphi process involving healthcare experts from various disciplines. Recommendations were structured to ensure compliance with international regulations and sustainability frameworks aligned with the One Health approach and Sustainable Development Goals (SDGs). Results: Key recommendations emphasize selecting gloves based on clinical needs and compliance with EN 455 standards. Sterile gloves are recommended for surgical and invasive procedures, while non-sterile gloves are suitable for routine care involving contact with blood and other body fluids or contaminated surfaces. Proper practices include performing hand hygiene before and after glove use, avoiding glove reuse, and training healthcare providers on donning and removal techniques to minimize cross-contamination. Disposal protocols should follow local clinical waste management regulations, promoting sustainability through recyclable or biodegradable materials whenever feasible. Conclusions: These consensus-based guidelines aim to enhance infection control, improve the safety of patients and healthcare workers, and minimize environmental impact. By adhering to these evidence-based practices, grounded in European regulations, healthcare settings can establish safe and sustainable glove management systems that serve as a model for global practices.